Stable isotope analysis of trophic structure, energy flow and spatial variability in a large ultraoligotrophic lake in Northwest Patagonia - Arcagni, Marina (2015)
The food web structure of the largest lake in northwest Patagonia, Lake Nahuel Huapi (area 557km2), was investigated. Fish, benthic macroinvertebrates, plankton and primary producers were analyzed for stable nitrogen (δ15N) and carbon (δ13C) isotopes in three sites with contrasting morphometry and environmental characteristics. δ15N and δ13C revealed a similar food web structure between basins but with distinct isotopic baselines. The SIAR (Stable Isotope Analysis in R) mixing model was used to study potential food sources (benthic or pelagic) for adult fish. Results indicated that energy flow to fish from both habitats is different for each site and species, and does not depend on the basin morphometry. An ontogenetic shift in the carbon source and trophic level was observed in some of the fish species, revealing a coupling between the pelagic and bentho-littoral habitats of the lake. Our findings complement the existing literature on trophic interactions between introduced and native fish, and provide novel information on plankton composition, food web structure and energy flow in a large lake of North Patagonia that can be extrapolated to other understudied lakes in the area.